Service Quality and E-Health Literacy Impact on Elderly Patient Loyalty at Hospital X - Pratiwi Utami; Ardi Ardi; Dewi Sri Surya Waisan; Richard Andre Sumaryo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The aging population increasingly relies on healthcare services, demanding hospitals to identify factors influencing elderly patients' revisit intentions. However, limited studies integrate service quality and digital literacy factors. Thus, this research addresses how service quality dimensions and e-health literacy affect elderly patients' revisit intentions mediated by customer perceived value (CPV) and customer satisfaction (CS). The objectives were to examine the direct and indirect effects of service quality and e-health literacy on revisit intention, with CPV and CS as mediators. A cross-sectional survey employing standardized questionnaires was conducted among approximately 300 elderly outpatients at Hospital X. Partial Least Squares Structural Equation Modeling (PLS-SEM) was utilized to analyze the data. Results demonstrated significant positive effects of service quality on both CPV and CS, while e-health literacy positively influenced CPV. CPV significantly predicted CS, and CS was the strongest predictor of revisit intention, fully mediating the effects of service quality and CPV on revisit intention. The key significant path coefficients were service quality to satisfaction (β ≈ .50, p<.01), CPV to satisfaction (β ≈ .60, p<.01), and satisfaction to revisit intention (β ≈ .52, p<.001). These findings highlight the crucial role of enhancing service quality and e-health literacy among elderly patients to improve their perceived value and satisfaction, ultimately increasing revisit intentions. The implications suggest healthcare management should prioritize high-quality services and digital health literacy programs for elderly patients.